Sensitive Analysis of Azelnidipine and Related Derivative in Human Plasma by Ultra-Performance Liquid Chromatography-Tandam Mass Spectrometry - Suneetha1, G.; Venkateswarlu1, P.; Prasad2, P.S.S. (Asian Journal of Chemistry, 2013)
A rapid and sensitive method for analysis of azelnidipine in human plasma by ultra-performance liquid chromatography tandem mass spectrometry is presented. After pretreatment of a plasma sample by solid-phase extraction, azelnidipine was analyzed by the system with a C18 column. This method gave satisfactory recovery rates, reproducibility and good linearity of calibration curve in the range of 0.01-10 ng/mL for quality control samples spiked with azelnidipine. The detection limit was as low as 1 pg/mL. This method seems very useful in forensic and clinical toxicology and pharmacokinetic studies.